2013
DOI: 10.1590/s0100-06832013000500003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between detailed digital and conventional soil maps of an area with complex geology

Abstract: SUMMARYSince different pedologists will draw different soil maps of a same area, it is important to compare the differences between mapping by specialists and mapping techniques, as for example currently intensively discussed Digital Soil Mapping. Four detailed soil maps (scale 1:10.000) of a 182-ha sugarcane farm in the county of Rafard, São Paulo State, Brazil, were compared. The area has a large variation of soil formation factors. The maps were drawn independently by four soil scientists and compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…Another important factor is that accuracy and effectiveness of surveys conducted conventionally are contingent upon the ability of the pedologist. Indeed Bazaglia Filho et al (2013) showed differences in maps developed between five pedologists, which show the importance of increasing accuracy through geotechnologies, as indicated in the present study.…”
Section: General Characteristics Of the Digital Soil Map (Dsm) And Cosupporting
confidence: 66%
“…Another important factor is that accuracy and effectiveness of surveys conducted conventionally are contingent upon the ability of the pedologist. Indeed Bazaglia Filho et al (2013) showed differences in maps developed between five pedologists, which show the importance of increasing accuracy through geotechnologies, as indicated in the present study.…”
Section: General Characteristics Of the Digital Soil Map (Dsm) And Cosupporting
confidence: 66%
“…(Cipra, 1973) Digital application of environmental similarity method Legros andBonneric (1979) 1980s Soil geostatistics Hajrasuliha et al (1980), Burgess and Webster (1980) Geographical information system Burrough (1986 Pedometrics: nonlinear geostatistics, fuzzy clustering, uncertainty analysis McBratney and Gruijter (1992), Odeh et al (1992b) Digital terrain modelling Gallant and Wilson (1996) Environmental correlation & cloprt model Moore et al (1993), McKenzie and Ryan (1999) Mapping using reference area Lagacherie et al (1995) Mapping using expert knowledge and expert system Skidmore et al (1996), Zhu et al (1997) Use of data mining tools Pachepsky et al (1996) (2014) Digital soil mapping has transformed soil survey and cartography more than anything else in recent times, and it is being tested and routinely used in soil mapping programmes around the world. Several studies have shown that digital soil mapping produces comparable or more accurate maps compared to conventional mapping (Bazaglia Filho et al, 2013;Collard et al, 2014). Lorenzetti et al (2015) compared 1:5,000,000 map of Italian soil regions and digital soil mapping at 1 km grid resolution in predicting the WRB reference soil groups (RSGs).…”
Section: Digital Soil Mappingmentioning
confidence: 99%
“…Bazaglia Filho et al [9] also reached a range from 12% to 35% agreement between the traditional and digital soil map in an area of tropical soils. In that occasion, only terrain attributes derived from relif were used for soil classes prediction.…”
Section: Supervised Classification and Digital Soil Mapsmentioning
confidence: 82%
“…There is an indication that the results vary according to some parameters such as prediction co-variables, the scale, the complexity of the area and the statistical methods [9,65]. Although [34] have reached 91% of agreement for Oxisol class in their study, Alfisol and Ultisol classes just reached 46% of concordance between conventional and digital maps.…”
Section: Supervised Classification and Digital Soil Mapsmentioning
confidence: 91%
See 1 more Smart Citation